Caracterização de resíduo sólido formado em biodiesel de sebo bovino - Pivesso, Paulo Roberto (2011)
Biodiesel production has increased over the last decade because of the benefits associated with this fuel, including renewability, domestic feedstock, lower toxicity, and biodegradability. From 2008, the use of beef tallow as a feedstock for biodiesel production in Brazil has increased in significance, representing the second largest source of biodiesel, after soybeans. However, the performance of biodiesel in cold weather conditions is worse than diesel because of deposition of insoluble at low temperatures, accelerating the plugging of fuel filters and injectors of the vehicle engine. Studies have been conducted on beef tallow biodiesel, mostly related to the properties of thermal and oxidative stability. However, few studies have described the nature of the precipitate formed and its influence on product quality. Research suggests that the cause of deposition is related to the nature of saturated esters and monoacylglycerols as inducing agents. This study monitored the levels of mono-, diand triacylglycerols, the oxidation stability and the cold filter plugging point (CFPP) in beef tallow biodiesel samples from two commercial producers in Brazil for a period of twelve months. Filtered precipitates were analyzed by comparative techniques of GCFID, HPLC-UV/VIS, HPLC-MS-IT-TOF and TG to verify the nature, using monopalmitin and monostearin as reference standards. The formation of precipitate reduced the levels of monoacylglycerols in the beef tallow biodiesel. GC-FID and LCMS- IT-TOF results confirmed the nature of the deposit as saturated monoacylglycerols, predominantly monostearin and monopalmitin as the second major component. Moreover the TG analysis of the residue indicated similar thermal decomposition of the reference standards. The precipitate did not affect the oxidation stability of beef tallow biodiesel and the CFPP characteristic of blends up B60. However, the presence of iron reduced significantly the oxidation stability of biodiesel